Teacher Perceptions Towards the Use of Multimodal Digital Storytelling In Teaching Speaking Skills In an EFL Classroom - Nenden Nur Humairah; Yustika Nurfajriah; Irsyad Nugraha (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores teachers’ perceptions of the use of multimodal digital storytelling in teaching speaking skills in an English as a Foreign Language (EFL) classroom. The study aims to examine how the strategy is implemented in speaking instruction and how teachers perceive its effectiveness in supporting students’ oral communication. This research employed a qualitative case study design involving two English teachers who have experience integrating this approach into classroom activities. Data were collected through semi-structured interviews and analyzed using thematic analysis to identify patterns related to classroom implementation and perceived benefits. The findings show that teachers apply several stages in the learning process, including introducing storytelling concepts, guiding students in preparing scripts, producing story videos, and presenting the final projects. Through these activities, students combine images, narration, text, and audio while practicing speaking. Teachers reported improvements in students’ fluency, pronunciation, vocabulary use, confidence, engagement, and motivation. However, challenges such as limited technological resources, differences in students’ digital literacy, and time constraints were also identified. Focusing on teachers’ perspectives, this study highlights the pedagogical potential of multimodal storytelling as an interactive and student-centered approach for developing speaking skills in EFL classrooms.